Melissa officinalis L. as a Nutritional Strategy for Cardioprotection - Draginic, Nevena; Jakovljevic, Vladimir; Andjic, Marijana; Jeremic, Jovana; Srejovic, Ivan; Rankovic, Marina; Tomovic, Marina; Nikolic Turnic, Tamara; Svistunov, Andrey; Bolevich, Sergey; Milosavljevic, Isidora (Frontiers in Physiology, 2021)
This review aimed to provide a summary on the traditional uses, phytochemistry, and pharmacological activities in the cardiovascular system and cardiotoxicity of Melissa officinalis (MO), with the special emphasis on the protective mechanisms in different cardiovascular pathologies. Melissa officinalis is a perennial aromatic herb commonly known as lemon balm, honey balm or bee balm which belongs to Lamiaceae family. Active components are mainly located in the leaves or essential oil and include volatile compounds, terpenoid (monoterpenes, sesquiterpenes, triterpens) and polyphenolic compounds (rosmarinic acid, caffeic acid, protocatechuic acid, quercitrin, rhamnocitrin, luteolin). For centuries, MO has been traditionally used as a remedy for memory, cognition, anxiety, depression and heart palpitations. Up until now several beneficial cardiovascular effects of MO in the form of extracts (aqueous, alcoholic and hydroalcoholic) essential oil, and isolated compounds, have been confirmed in preclinical animal studies, such as antiarrhythmogenic, negative chronotropic and dromotropic, hypotensive, vasorelaxant, and infarct size reducing effects. Nonetheless, MO effects on heart palpitations are the only ones confirmed in human subjects. The main mechanisms proposed for the cardiovascular effects of this plant are antioxidant free radical scavenging properties of MO polyphenols, amelioration of oxidative stress, anti-inflammatory effects, activation of M2 and antagonism of β1 receptors in the heart, blockage of voltage dependent Ca2+ channels, stimulation of endothelial NO synthesis, prevention of fibrotic changes etc. Additionally, the main active ingredient of MO rosmarinic acid (RA), per se, has shown substantial cardiovascular effects. Due to the vast of encouraging data from animal studies, this plant, as well as the main ingredient RA should be considered and furtherly investigated as a tool for cardioprotection and adjuvant therapy in patients suffering from cardiovascular diseases.